Thermally conductive composition and thermally conductive sheet using same

The thermally conductive composition using urethane resin and zeolite addresses the limitations of silicone resin-based materials by providing a flexible, heat-resistant, and moisture-resistant thermally conductive sheet with enhanced thermal conductivity.

JP7661032B2Active Publication Date: 2025-04-14DEXERIALS CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020194002
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-24
Publication Date
2025-04-14
Estimated Expiration
2040-11-24

AI Technical Summary

Technical Problem

Existing thermally conductive materials using silicone resin generate siloxane gas, leading to defective contacts in electronic devices, and lack flexibility, heat resistance, and moisture resistance.

Method used

A thermally conductive composition comprising a binder component made of urethane resin, carbon fibers, a thermally conductive filler other than carbon fibers, a water-absorbing agent containing zeolite, and a dispersing agent, which provides excellent dispersibility and curability.

Benefits of technology

The thermally conductive sheet produced from this composition exhibits excellent flexibility, heat resistance, moisture resistance, and thermal conductivity, maintaining performance even after aging treatments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661032000003
    Figure 0007661032000003
  • Figure 0007661032000004
    Figure 0007661032000004
  • Figure 0007661032000005
    Figure 0007661032000005
Patent Text Reader

Abstract

To provide a thermally conductive composition which enables formation of a thermally conductive sheet having good flexibility, heat resistance and moisture resistance.SOLUTION: A thermally conductive composition contains a binder component 2 composed of an urethane resin, carbon fibers 3, thermally conductive fillers 4 other than the carbon fiber, a water absorbent and a dispersant, in which the water absorbent contains zeolite, and a content of the water absorbent is 2-15 pts.mass with respect to 100 pts.mass of the binder component 2. The thermally conductive sheet 1 is composed of the thermally conductive composition.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a thermally conductive composition and a thermally conductive sheet using the same. [Background technology]

[0002] Thermally conductive materials (e.g., thermally conductive sheets) are known that are interposed between a heat generating body such as an electronic component and a heat sink such as a heat sink fin. This type of thermally conductive material is used to efficiently transfer heat generated from the heat generating body to the heat sink. Such thermally conductive materials mainly contain a resin component that serves as a base material and a thermally conductive filler that is dispersed in the resin component.

[0003] In order to provide durability to thermally conductive materials, silicone resin is often used as the resin component (see, for example, Patent Documents 1 and 2). Thermally conductive materials using acrylic resin as the resin component are also known (see, for example, Patent Document 3).

[0004] By the way, when the thermally conductive sheet has a low hardness, it can be adhered to the heat generating components and the heat dissipation member to obtain a wide contact area, and therefore, heat can be efficiently transferred. In addition, when the thermally conductive sheet has a low hardness, even if heat generating components of different heights are mounted at high density, the sheet can follow the height of the heat generating components, and the heat conductive sheet absorbs the unevenness of the height of the heat generating components, so that the heat conductive sheet and the heat generating components are adhered to each other, and a wide contact area can be obtained. For such a low-hardness thermally conductive sheet, a silicone resin (rubber-like or gel-like) having high flexibility is usually used. However, a thermally conductive composition using a silicone resin generates siloxane gas (for example, a low-molecular-weight siloxane gas such as a cyclic siloxane gas). This siloxane gas can cause contact failures in electronic devices. Therefore, a thermally conductive composition using a non-silicone resin that does not generate siloxane gas is desired. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-216387 A [Patent Document 2] JP 2011-241403 A [Patent Document 3] Patent No. 6692512 Summary of the Invention [Problem to be solved by the invention]

[0006] The present technology has been proposed in view of the above-mentioned conventional situation, and aims to provide a thermally conductive composition capable of forming a thermally conductive sheet having good flexibility, heat resistance, and moisture resistance, and a thermally conductive sheet using the same. [Means for solving the problem]

[0007] The thermally conductive composition according to the present technology includes a binder component made of a urethane resin, carbon fiber, a thermally conductive filler other than carbon fiber, a water absorbing agent, and a dispersing agent, the water absorbing agent includes zeolite, and the content of the water absorbing agent is 2 to 15 parts by mass relative to 100 parts by mass of the binder component.

[0008] The thermally conductive sheet according to the present technology comprises the thermally conductive composition. Effect of the Invention

[0009] According to the present technology, it is possible to provide a thermally conductive sheet having good flexibility, heat resistance and moisture resistance. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view showing an example of a carbon fiber covered with an insulating film. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a thermally conductive sheet. [Diagram 3] FIG. 3 is a cross-sectional view showing an example of a thermally conductive sheet. [Figure 4]FIG. 4 is a cross-sectional view showing an example of a semiconductor device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] <Thermal conductive composition> The thermally conductive composition according to the present technology includes a binder component made of a urethane resin, carbon fiber, a thermally conductive filler other than carbon fiber, a water absorbing agent, and a dispersing agent, the water absorbing agent includes zeolite, and the content of the water absorbing agent is 2 to 15 parts by mass relative to 100 parts by mass of the binder component.

[0012] The thermally conductive composition according to the present technology uses a binder component made of a urethane resin, and therefore, compared to the case where a silicone resin is used as the binder component, it is possible to prevent the generation of siloxane gas caused by the silicone resin, for example, low molecular weight siloxane gas that may cause contact failure. In addition, the thermally conductive composition according to the present technology has good dispersibility and curability. By using such a thermally conductive composition, a thermally conductive sheet having good flexibility, heat resistance, and moisture resistance can be obtained.

[0013] <Binder component made of urethane resin> The thermally conductive composition according to the present technology contains a binder component made of a urethane resin. The urethane resin may be used alone or in combination of two or more kinds. The urethane resin as the binder component is made of, for example, a polyol and a polyisocyanate.

[0014] Examples of the polyol include alkylene-type, polycarbonate-type, polyester-type, and polyether-type polyol compounds, and specific examples thereof include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polycarbonate diol, polyester diol, and polyether diol.

[0015] Examples of the polyisocyanate include diisocyanates such as isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, and diphenylmethane-4,4'-diisocyanate.

[0016] The weight average molecular weight (Mw) of the urethane resin can be in the range of 10,000 to 100,000, for example.

[0017] The content of the urethane resin in the binder component is preferably 90% by mass or more, more preferably 95% by mass or more, and particularly preferably 100%.

[0018] <Thermal conductive filler> The thermally conductive composition contains, as a thermally conductive filler, carbon fiber and a thermally conductive filler other than carbon fiber.

[0019] [Carbon fiber] Examples of the carbon fiber that can be used include pitch-based carbon fiber, PAN-based carbon fiber, carbon fiber obtained by graphitizing PBO fiber, and carbon fiber synthesized by arc discharge, laser evaporation, CVD (chemical vapor deposition), CCVD (catalytic chemical vapor deposition), etc. Among these, pitch-based carbon fiber is preferred from the viewpoint of thermal conductivity.

[0020] The average fiber length (average major axis length) of the carbon fibers can be, for example, 50 to 250 μm, or may be 75 to 200 μm, or may be 90 to 170 μm. The average fiber diameter (average minor axis length) of the carbon fibers can also be appropriately selected depending on the purpose, and can be, for example, 4 to 20 μm, or may be 5 to 14 μm. The aspect ratio (average major axis length / average minor axis length) of the carbon fibers can be appropriately selected depending on the purpose, and can be, for example, 9 to 30. The average major axis length and average minor axis length of the carbon fibers can be measured, for example, by a microscope or a scanning electron microscope (SEM).

[0021] A specific example of the carbon fiber is XN-100-20M (pitch-based carbon fiber having an average fiber diameter of 9 μm and an average fiber length of 200 μm) manufactured by Nippon Graphite Fiber Co., Ltd.

[0022] Fig. 1 is a perspective view showing an example of carbon fiber 3B coated with an insulating coating 5. From the viewpoint of improving the insulation of the thermally conductive sheet 1, the surface of the carbon fiber 3B may be coated with an insulating coating 5 as shown in Fig. 1. In this manner, an insulating coated carbon fiber can be used as the carbon fiber. The insulating coated carbon fiber 6 has carbon fiber 3B and an insulating coating 5 on at least a part of the surface of the carbon fiber 3B, and may contain other components as necessary.

[0023] The insulating film 5 is made of a material having electrical insulation properties, and is formed of, for example, silicon oxide or a cured product of a polymerizable material. The polymerizable material is, for example, a radically polymerizable material, and examples thereof include a polymerizable organic compound and a polymerizable resin. The radically polymerizable material can be appropriately selected according to the purpose as long as it is a material that undergoes radical polymerization using energy, and examples thereof include a compound having a radically polymerizable double bond. Examples of the radically polymerizable double bond include a vinyl group, an acryloyl group, and a methacryloyl group. The number of radically polymerizable double bonds in the compound having a radically polymerizable double bond is preferably two or more from the viewpoint of strength including heat resistance and solvent resistance. Examples of the compound having two or more radically polymerizable double bonds include divinylbenzene (DVB) and a compound having two or more (meth)acryloyl groups. The radically polymerizable material may be used alone or in combination of two or more. The molecular weight of the radically polymerizable material can be appropriately selected depending on the purpose and can be, for example, in the range of 50 to 500. When the insulating coating 5 is formed from a cured product of a polymerizable material, the content of structural units derived from the polymerizable material in the insulating coating 5 can be, for example, 50 mass % or more, or can also be 90 mass % or more.

[0024] The average thickness of the insulating coating 5 can be appropriately selected depending on the purpose, and from the viewpoint of realizing high insulation properties, it can be 50 nm or more, or may be 100 nm or more, or may be 200 nm or more. The upper limit of the average thickness of the insulating coating 5 can be, for example, 1000 nm or less, or may be 500 nm or less. The average thickness of the insulating coating 5 can be determined, for example, by observation with a transmission electron microscope (TEM).

[0025] Methods for covering the carbon fiber 3B with the insulating coating 5 include, for example, a sol-gel method, a liquid phase deposition method, a polysiloxane method, and a method of forming an insulating coating 5 made of a cured product of a polymerizable material on at least a portion of the surface of the carbon fiber 3B, as described in paragraphs 0073 to 0089 of JP2018-98515A.

[0026] [Thermal conductive fillers other than carbon fiber] The thermally conductive filler other than carbon fiber can be selected from known materials in consideration of the desired thermal conductivity and packing property, and examples thereof include metal hydroxides such as aluminum hydroxide and magnesium hydroxide, metals such as aluminum, copper, and silver, metal oxides such as alumina and magnesium oxide, metal nitrides such as aluminum nitride, boron nitride, and silicon nitride, carbon nanotubes, and metal silicon. The thermally conductive filler other than carbon fiber may be used alone or in combination of two or more kinds.

[0027] From the viewpoint of thermal conductivity, the thermally conductive composition preferably contains at least aluminum hydroxide as a thermally conductive filler other than carbon fiber, and aluminum hydroxide may be used in combination with hydraulic alumina. From the viewpoint of the specific gravity of the thermally conductive sheet, the average particle size (D50) of the aluminum hydroxide is preferably less than 30 μm, may be 0.1 to 10 μm, or may be 5 to 10 μm. From the viewpoint of the specific gravity of the thermally conductive sheet, the average particle size (D50) of the hydraulic alumina is preferably 1 to 30 μm, may be 5 to 20 μm, or may be 10 to 20 μm.

[0028] In this specification, the average particle size of the thermally conductive filler refers to the particle size at which the cumulative value of the cumulative curve of particle size values ​​from the small particle size side of the particle size distribution is 50% when the entire particle size distribution of the thermally conductive filler is 100%. Note that the particle size distribution (particle size distribution) in this specification is determined on a volume basis. For example, a method of measuring the particle size distribution can be a method using a laser diffraction type particle size distribution measuring device.

[0029] Specific examples of thermally conductive fillers other than carbon fiber include BK-112 (hydraulic alumina) manufactured by Sumitomo Chemical Co., Ltd., and BF803 (aluminum hydroxide) and BX053T (aluminum hydroxide) manufactured by Nippon Light Metal Co., Ltd.

[0030] The total content of the carbon fiber and the thermally conductive filler other than the carbon fiber in the thermally conductive composition can be appropriately determined according to the desired thermal conductivity. For example, the volume content of the carbon fiber and the thermally conductive filler other than the carbon fiber in the thermally conductive composition can be 60 to 90% by volume. By setting the volume content of the thermally conductive filler in the thermally conductive composition to 60% by volume or more, sufficient thermal conductivity tends to be easily obtained. In addition, by setting the volume content of the thermally conductive filler in the thermally conductive composition to 90% by volume or less, the carbon fiber and the thermally conductive filler other than the carbon fiber can be filled more reliably. In addition, when comparing the thermal conductivity of the carbon fiber and the thermally conductive filler other than the carbon fiber, the dependence on the carbon fiber is large. Therefore, it is considered that the ratio of the thermally conductive filler other than the carbon fiber (for example, aluminum hydroxide or hydraulic alumina) to the total amount of the carbon fiber and the thermally conductive filler other than the carbon fiber does not have a large effect.

[0031] In the thermally conductive composition, the content of the thermally conductive filler other than carbon fiber can be, for example, 80 parts by mass or more, 150 parts by mass or more, 200 parts by mass or more, 250 parts by mass or more, 300 parts by mass or more, 350 parts by mass or more, or 400 parts by mass or more, when the content of the binder component is 100 parts by mass. In addition, the content of the thermally conductive filler other than carbon fiber in the thermally conductive composition can be, for example, 600 parts by mass or less, or 550 parts by mass or less, when the content of the binder component is 100 parts by mass.

[0032] <Dispersant> The thermally conductive composition contains a dispersant for improving the dispersibility of the carbon fiber and the thermally conductive filler other than the carbon fiber. The dispersant may be used alone or in combination of two or more. When the thermally conductive composition contains a binder component made of a urethane resin, and this urethane resin is made of a high-viscosity polyol, a titanate-based dispersant is useful when the high-viscosity polyol is highly filled with the thermally conductive filler. In addition, the titanate-based dispersant has good coupling with the thermally conductive filler and contributes to further improving flexibility. Therefore, it is preferable to use a titanate-based dispersant (titanate-based coupling agent) as the dispersant.

[0033] Examples of titanate coupling agents include carboxylic acid-type titanate coupling agents such as isopropyl triisostearoyl titanate; pyrophosphate-type titanate coupling agents such as isopropyl tris(dioctyl pyrophosphate) titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, tris(dioctyl pyrophosphate)ethylene titanate, and isopropyl dioctyl pyrophosphate titanate; and isopropyl tris(dodecyl benzene sulfate-type titanate coupling agents such as tetraoctylbis(ditridecylphosphite)titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, tetraisopropylbis(dioctylphosphite)titanate, and amine-type titanate coupling agents such as isopropyltri(N-aminoethylaminoethyl)titanate. Among these, carboxylic acid-type titanate coupling agents are preferred, and isopropyltriisostearoyltitanate is more preferred.

[0034] An example of a commercially available dispersant is KR-TTS (titanate coupling agent) manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0035] In the thermally conductive composition, the content of the dispersant can be 1.0 parts by mass or more, 1.5 parts by mass or more, 2.0 parts by mass or more, 2.3 parts by mass or more, 2.4 parts by mass or more, or 2.8 parts by mass or more, when the content of the binder component is 100 parts by mass. In addition, in the thermally conductive composition, the content of the dispersant can be 10.0 parts by mass or less, 8.0 parts by mass or less, 6.0 parts by mass or less, or 4.0 parts by mass or less, when the content of the binder component is 100 parts by mass. In addition, the content of the dispersant can be in the range of 2.3 to 2.8 parts by mass, when the content of the binder component is 100 parts by mass.

[0036] From the viewpoint of suppressing the generation of siloxane gas, the thermally conductive composition preferably does not substantially contain a silane-based dispersant (silane coupling agent). The content of the silane-based dispersant (silane coupling agent) in the thermally conductive composition is preferably 5% by mass or less, more preferably 2% by mass or less, even more preferably 1% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0% by mass.

[0037] <Water absorbent> When the thermally conductive composition according to the present technology is highly filled with a thermally conductive filler containing a large amount of moisture, the moisture from the thermally conductive filler may inhibit the curing of polyol and polyisocyanate, which are raw materials of the urethane resin, which is a binder component. In addition, since the moisture from the urethane resin can also act as a foaming agent, it is preferable that the moisture content is as low as possible. In consideration of these points, the thermally conductive composition according to the present technology contains at least zeolite as a water absorbing agent.

[0038] The crystal structure of the zeolite is not particularly limited, and for example, A type, X type, LSX type, etc. can be selected. The shape of the zeolite can be selected from spherical (bead-like), cylindrical (pellet-like), powdery, etc. Zeolite is preferably in a powder form of 10 μm or less. By making the average particle size of the zeolite 10 μm or less, it is possible to suppress the influence on the orientation of the carbon fiber and the decrease in thermal conductivity. Specific examples of zeolite that can selectively adsorb moisture are preferable, and include Zeolum (registered trademark) A-3 series and A-4 series manufactured by Tosoh Corporation, and 3A series and 4A series manufactured by Union Showa Co., Ltd. In particular, molecular sieve 3A-B powder manufactured by Union Showa Co., Ltd., which is a highly water-absorbent type, is preferable.

[0039] In addition, hydraulic alumina may be used in combination with zeolite as the water absorbent. As described above, hydraulic alumina also functions as a thermally conductive filler. However, hydraulic alumina tends to have a poorer water absorption effect than zeolite. Therefore, when hydraulic alumina is used alone as the water absorbent, it is necessary to use a larger amount of hydraulic alumina than when zeolite is used alone. In addition, if too much hydraulic alumina is added to the thermally conductive composition, there is a risk that the flame retardancy of the thermally conductive composition when it is made into a thermally conductive sheet may be affected. For these reasons, it is preferable to use zeolite alone or a combination of zeolite and hydraulic alumina as the water absorbent.

[0040] The total content of the water absorbing agent in the thermally conductive composition is 2 to 15 parts by mass relative to 100 parts by mass of the binder component. When the content of the water absorbing agent in the thermally conductive composition is 2 parts by mass or more relative to 100 parts by mass of the binder component, the curability becomes good. Also, when the content of the water absorbing agent in the thermally conductive composition is 15 parts by mass or less relative to 100 parts by mass of the binder component, good thermal conductivity can be maintained.

[0041] When zeolite is used alone as the water absorbing agent, the content of the water absorbing agent in the thermally conductive composition may be 2.1 parts by mass or more, 2.2 parts by mass or more, 2.31 parts by mass or more, or 2.35 parts by mass or more relative to 100 parts by mass of the binder component. Here, since zeolite is generally porous and has poor thermal conductivity, if the amount of zeolite in the thermally conductive composition becomes too large, the kneadability of the thermally conductive composition deteriorates, and when the thermally conductive composition is made into a sheet, the sheet may become too hard, and the thermal conductivity of the sheet may also decrease. In addition, since zeolite is not flame retardant, if the amount of zeolite in the thermally conductive composition becomes too large, the flame retardancy of the thermally conductive composition when made into a sheet may decrease. Considering these points, when zeolite is used alone as a water absorbing agent, the content of the water absorbing agent in the thermally conductive composition is, for example, preferably 10 parts by mass or less per 100 parts by mass of the binder component, and can also be 8 parts by mass or less, 6 parts by mass or less, or 4 parts by mass or less.

[0042] When zeolite and hydraulic alumina are used in combination as the water absorbing agent, the total content of the water absorbing agent in the thermal conductive composition may be 9.0 parts by mass or more, 10.0 parts by mass or more, or 11.0 parts by mass or more relative to 100 parts by mass of the binder component. When zeolite and hydraulic alumina are used in combination as the water absorbing agent, the total content of the water absorbing agent in the thermal conductive composition may be 14.0 parts by mass or less, 13.0 parts by mass or less, 12.0 parts by mass or less, or 11.5 parts by mass or less relative to 100 parts by mass of the binder component.

[0043] <Flame retardants> The thermally conductive composition may further contain a flame retardant in order to improve the flame retardancy when formed into a sheet. As the flame retardant, a phosphorus-based flame retardant is preferable. As the phosphorus-based flame retardant, an organic phosphorus-based flame retardant containing phosphorus can be mentioned. As the phosphorus-based flame retardant, for example, a phosphorus ester, a metal phosphinate, a melamine phosphate compound, an ammonium phosphate compound, etc. can be mentioned. Among these phosphorus-based flame retardants, from the viewpoint of flame retardancy, a flame retardant made of a metal phosphinate is preferable, and a flame retardant made of a dialkyl phosphinate is also preferable.

[0044] Specific examples of the dialkylphosphinate include aluminum trisdiethylphosphinate, aluminum trismethylethylphosphinate, aluminum trisdiphenylphosphinate, zinc bisdiethylphosphinate, zinc bismethylethylphosphinate, zinc bisdiphenylphosphinate, titanyl bisdiethylphosphinate, titanium tetrakisdiethylphosphinate, titanyl bismethylethylphosphinate, titanium tetrakismethylethylphosphinate, titanyl bisdiphenylphosphinate, and titanium tetrakisdiphenylphosphinate.

[0045] The average particle size of the flame retardant can be, for example, 1 to 100 μm, or can also be 1 to 30 μm.

[0046] Examples of flame retardant products include the EXOLIT (registered trademark) OP series manufactured by Clariant, specifically, EXOLIT (registered trademark) OP930, 935, 945TP, 1230, 1240, 1312, 1400, and the like.

[0047] When the thermally conductive composition contains a flame retardant, the content of the flame retardant in the thermally conductive composition can be, for example, 2.0 parts by mass or more, 4.0 parts by mass or more, 6.0 parts by mass or more, 8.0 parts by mass or more, or 9.0 parts by mass or more, when the content of the binder component is 100 parts by mass. When the thermally conductive composition contains a flame retardant, the upper limit of the content of the flame retardant in the thermally conductive composition can be, for example, 20.0 parts by mass or less, 16.0 parts by mass or less, 12.0 parts by mass or less, or 10.0 parts by mass or less, when the content of the binder component is 100 parts by mass.

[0048] <Antioxidants> The thermally conductive composition may further contain an antioxidant. For example, a hindered phenol-based antioxidant may be used as the antioxidant. Examples of the hindered phenol-based antioxidant include those having a structure represented by the following formula 1 as a hindered phenol skeleton. The hindered phenol-based antioxidant preferably has one or more skeletons represented by the following formula 1, and may have two or more skeletons represented by the following formula 1.

[0049] (Formula 1) [ka]

[0050] In formula 1, R 1 and R 2 represents a t-butyl group, and R 3 When represents a hydrogen atom (hindered type), R 1 represents a methyl group, and R 2 represents a t-butyl group, and R 3 When represents a hydrogen atom (semi-hindered type), R 1 represents a hydrogen atom, and R 2 represents a t-butyl group, and R 3represents a methyl group (unhindered type). From the viewpoint of long-term thermal stability in a high-temperature environment, a semi-hindered type or a hindered type is preferred. The hindered phenol-based antioxidant preferably has three or more skeletons represented by the above formula 1 in one molecule, and the three or more skeletons represented by formula 1 are linked by a hydrocarbon group or a group consisting of a combination of a hydrocarbon group, -O-, and -CO-. The hydrocarbon group may be linear, branched, or cyclic. The carbon number of the hydrocarbon group may be, for example, 3 to 8. The molecular weight of the hindered phenol-based antioxidant may be, for example, 300 to 850, or may be 500 to 800.

[0051] The hindered phenol-based antioxidant may have an ester bond in its structure. Examples of such phenol-based antioxidants include stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis[3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate], and 2,2'-dimethyl-2,2'-(2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diyl)dipropane-1,1'-diyl=bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propanoate]. In addition, the hindered phenol-based antioxidant may also be one that does not have an ester bond in its structure, such as 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane.

[0052] Commercially available phenolic antioxidants include Adeka STAB AO-30, Adeka STAB AO-50, Adeka STAB AO-60, Adeka STAB AO-80 (all manufactured by ADEKA Corporation), Irganox 1010, Irganox 1035, Irganox 1076, Irganox 1135 (all manufactured by BASF Corporation), etc. The phenolic antioxidants may be used alone or in combination of two or more kinds.

[0053] When the thermally conductive composition contains an antioxidant, the content of the antioxidant in the thermally conductive composition can be, for example, 0.1 parts by mass or more, or can be 0.5 parts by mass or more, relative to 100 parts by mass of the binder component. When the thermally conductive composition contains an antioxidant, the upper limit of the content of the antioxidant in the thermally conductive composition can be, for example, 10 parts by mass or less, 5 parts by mass or less, or 3 parts by mass or less, relative to 100 parts by mass of the binder component.

[0054] As described above, the thermally conductive composition according to the present technology includes a binder component made of a urethane resin, carbon fiber, a thermally conductive filler other than carbon fiber, a water absorbing agent, and a dispersant, and the water absorbing agent includes zeolite, and the content of the water absorbing agent is 2 to 15 parts by mass relative to 100 parts by mass of the binder component, so that the thermally conductive composition according to the present technology has good dispersibility and curability. In addition, the thermally conductive composition according to the present technology can have good thermal conductivity, flexibility, heat resistance, and moisture resistance when formed into a sheet.

[0055] The thermally conductive composition may further contain components other than the above-mentioned components as long as the effects of the present technology are not impaired.

[0056] The thermally conductive composition can be obtained, for example, by kneading the above-mentioned components using a kneader (such as a planetary kneader, a ball mill, or a Henschel mixer).

[0057] <Thermal conductive sheet> FIG. 2 is a cross-sectional view showing an example of a thermally conductive sheet. The thermally conductive sheet 1 is made of a cured product of the thermally conductive composition described above. For example, the thermally conductive sheet 1 is obtained by applying the thermally conductive composition described above to a desired thickness on a release film 11 formed of, for example, PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyolefin, polymethylpentene, glassine paper, or the like, and heating the composition to cure the binder component. The thickness of the thermally conductive sheet 1 (the thickness of the sheet body excluding the release film 11) can be appropriately selected depending on the purpose, and can be, for example, 0.05 to 5 mm.

[0058] 3 is a cross-sectional view showing an example of a thermally conductive sheet. The thermally conductive sheet 1 includes a binder component 2 made of a urethane resin, carbon fibers 3 oriented in the thickness direction B of the thermally conductive sheet 1, a thermally conductive filler 4 other than the carbon fibers 3, a water absorbing agent, and a dispersing agent.

[0059] By using the thermally conductive composition described above, the thermal conductivity of the thermally conductive sheet 1 can be 5.0 W / m·K or more, 5.5 W / m·K or more, 6.0 W / m·K or more, 7.0 W / m·K or more, 10.0 W / m·K or more, 12.0 W / m·K or more, 14.0 W / m·K or more, or 15.0 W / m·K or more. The upper limit of the thermal conductivity of the thermally conductive sheet 1 is not particularly limited, but can be, for example, 17.0 W / m·K or less. The thermal conductivity can be measured by the method described in the Examples below.

[0060] In addition, since the thermally conductive sheet 1 uses the above-mentioned thermally conductive composition, it has good flexibility. For example, it can withstand temperatures of 45° C. and a load of 1 kgf / cm 2 The ratio of the compression ratio (amount of change from the initial thickness of the thermal conductive sheet) when pressure is applied at 1000 MPa to the initial thickness of the thermal conductive sheet can be 5% or more. The upper limit of the compression ratio is not particularly limited, but can be, for example, 20% or less. The compression ratio can be measured by the method described in the Examples below.

[0061] Incidentally, a thermally conductive composition using a urethane resin as a binder component tends to have inferior heat resistance and moisture and heat resistance compared to a thermally conductive composition using a silicone resin as a binder component. Therefore, a thermally conductive sheet with poor reliability may deteriorate, for example, by aging treatment at 125°C, and become hard and inflexible like gypsum, and may dissolve (hydrolyze) due to moisture and dissolve when aging treatment is performed under conditions of 85°C and 85% relative humidity. On the other hand, the thermally conductive sheet 1 using the thermally conductive composition according to the present technology described above has good heat resistance reliability, does not solidify or liquefy, and can maintain thermal conductivity even after aging treatment. Specifically, the thermal conductivity of the thermally conductive sheet 1 after aging treatment can be 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, or 90% or more of the initial thermal conductivity (thermal conductivity of the thermally conductive sheet 1 before aging treatment). The heat resistance reliability can be measured by the method described in the examples below.

[0062] <Method of manufacturing thermally conductive sheet> The thermally conductive sheet 1 can be obtained, for example, by a method including the following steps A, B, and C.

[0063] <Process A> In step A, a resin composition for forming a thermally conductive sheet is prepared. The resin composition for forming a thermally conductive sheet can be prepared by uniformly mixing at least a binder component 2 made of a urethane resin, carbon fibers 3, a thermally conductive filler 4 other than the carbon fibers 3, a water absorbing agent containing zeolite, and a dispersing agent by a known method.

[0064] <Process B> In step B, a molded block is formed from the prepared resin composition for forming a thermally conductive sheet. Examples of the method for forming the molded block include extrusion molding and die molding. The extrusion molding and die molding methods are not particularly limited, and can be appropriately selected from various known extrusion molding and die molding methods according to the viscosity of the resin composition for forming a thermally conductive sheet and the properties required for the thermally conductive sheet.

[0065] For example, in an extrusion molding method, when the resin composition for forming a thermally conductive sheet is extruded through a die, or in a mold molding method, when the resin composition for forming a thermally conductive sheet is pressed into a mold, the binder component flows and the carbon fibers 3 are oriented along the flow direction.

[0066] The size and shape of the molded block can be determined according to the desired size of the thermally conductive sheet 1. For example, it may be a rectangular parallelepiped with a cross-sectional vertical dimension of 0.5 to 15 cm and a horizontal dimension of 0.5 to 15 cm. The length of the rectangular parallelepiped may be determined as necessary.

[0067] <Process C> In step C, the molded body block is sliced ​​into sheets to obtain a thermally conductive sheet 1. Carbon fibers are exposed on the surface (sliced ​​surface) of the sheet obtained by slicing. The thermally conductive sheet 1 obtained by slicing has a smoothed surface, which can improve adhesion with other members and improve thermal conductivity. In addition, the thermally conductive sheet 1 obtained by slicing has a smoothed surface, which can reduce thermal resistance. There is no particular limitation on the slicing method, and it can be appropriately selected from among known slicing devices depending on the size and mechanical strength of the molded body block. When the molding method is extrusion molding, the slicing direction of the molded body block is preferably 60 to 120 degrees relative to the extrusion direction, more preferably 70 to 100 degrees, and even more preferably 90 degrees (perpendicular) because some molded body blocks have carbon fibers oriented in the extrusion direction.

[0068] The method for producing a thermally conductive sheet is not limited to the above-mentioned example, and may further include a step D of pressing the sliced ​​surface after the step C, for example. By including the pressing step D in the method for producing a thermally conductive sheet, the surface of the sheet obtained in the step C is made smoother, and the adhesion to other members can be improved. As a pressing method, a pair of pressing devices consisting of a flat plate and a press head with a flat surface can be used. Pressing may also be performed with a pinch roll. The pressure during pressing may be, for example, 0.1 to 100 MPa. In order to further increase the effect of pressing and shorten the pressing time, pressing is preferably performed at a temperature equal to or higher than the glass transition temperature (Tg) of the binder component 2. For example, the pressing temperature may be 0 to 180°C, and may be within a temperature range of room temperature (for example, 25°C) to 100°C, or may be 30 to 100°C.

[0069] As described above, the thermally conductive sheet 1 is made of the thermally conductive composition described above, and therefore has good thermal conductivity, flexibility, heat resistance reliability, and flame retardancy. As described above, the thermally conductive sheet 1 has good thermal conductivity and flexibility, and can be applied to a heat dissipation structure in which the thermally conductive sheet 1 is sandwiched between a heat generating body and a heat dissipation member. Examples of the heat generating body include integrated circuit elements such as CPUs, GPUs (Graphics Processing Units), DRAMs (Dynamic Random Access Memory), and flash memories, as well as electronic components that generate heat in electric circuits, such as transistors and resistors. The heat generating body also includes components that receive optical signals, such as optical transceivers in communication devices. The heat dissipation member may be any member that conducts heat generated from the heat generating body and dissipates it to the outside, and examples of the heat dissipation member include heat sinks and heat spreaders that are used in combination with integrated circuit elements, transistors, optical transceiver housings, and the like. Examples of the heat dissipation member include heat sinks, coolers, die pads, printed circuit boards, cooling fans, Peltier elements, heat pipes, metal covers, housings, and the like.

[0070] FIG. 4 is a cross-sectional view showing an example of a semiconductor device. In actual use, for example, the thermally conductive sheet 1 from which the release film 11 shown in FIG. 2 has been peeled off can be mounted inside electronic components such as a semiconductor device or various electronic devices. The thermally conductive sheet 1 is mounted on a semiconductor device 50 built into various electronic devices, as shown in FIG. 4, for example, and is sandwiched between a heat generating body and a heat dissipation member. That is, the electronic device includes a heat generating body, a heat dissipation member, and the thermally conductive sheet 1 disposed between the heat generating body and the heat dissipation member. The semiconductor device 50 shown in FIG. 4 has at least an electronic component 51, a heat spreader 52, and a thermally conductive sheet 1, and the thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the electronic component 51. By using the thermally conductive sheet 1, the semiconductor device 50 has high heat dissipation properties. In addition, the thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the heat sink 53, and together with the heat spreader 52, the thermally conductive sheet 1 constitutes a heat dissipation member that dissipates heat from the electronic component 51. The location where the thermally conductive sheet 1 is mounted is not limited to between the heat spreader 52 and the electronic component 51 or between the heat spreader 52 and the heat sink 53, but can be appropriately selected depending on the configuration of the electronic device or semiconductor device.

[0071] The present technology can also be applied to products equipped with the above-mentioned heat dissipation structure. Examples of products equipped with such heat dissipation structures include personal computers, server devices, mobile phones, wireless base stations, and ECUs (Electronic Control Units) used to control electrical components such as engines, power transmission systems, steering systems, and air conditioners in transport machines such as automobiles. EXAMPLES

[0072] Examples of the present technology will be described below. In the examples, a thermally conductive composition was obtained from the raw materials shown in Table 1. The thermally conductive composition was evaluated for dispersibility and curability. The thermally conductive sheet obtained from the thermally conductive composition was evaluated in each of the ways shown in Table 1. Note that the present technology is not limited to the following examples.

[0073] <Preparation of Thermally Conductive Composition> The raw materials used in this example are as follows:

[0074] <Binder components> A urethane resin made of polyisocyanate (a mixture of isophorone diisocyanate and hexamethylene diisocyanate) and polyol.

[0075] <Thermal conductive filler> Carbon fiber (pitch-based carbon fiber with an average fiber diameter of 9 μm and an average fiber length of 200 μm, product name: XN-100-20M, manufactured by Nippon Graphite Fiber Co., Ltd.) Hydraulic alumina (average particle size 17.5μm, product name: BK-112, manufactured by Sumitomo Chemical Co., Ltd.) Aluminum hydroxide (average particle size 10 μm, product name: BF803, manufactured by Nippon Light Metal Co., Ltd.) Aluminum hydroxide (average particle size 6.9 μm, product name: BX053T, manufactured by Nippon Light Metal Co., Ltd.)

[0076] <Water absorbent> Zeolite (product name: 3AB, manufactured by Union Showa)

[0077] <Dispersant> Titanate coupling agent (product name: KR-TTS, manufactured by Ajinomoto Fine-Techno Co., Ltd.)

[0078] <Flame retardants> Phosphorus-based flame retardant (average particle size 10 μm, product name: OP930, manufactured by Clariant)

[0079] <Antioxidants> Hindered phenol antioxidant (product name: AO-80, manufactured by ADEKA)

[0080] In each of the examples and comparative examples, the components shown in Table 1 were mixed to prepare a thermally conductive composition. The thermally conductive composition was poured into a mold (opening: 50 mm x 50 mm) having a rectangular parallelepiped internal space by extrusion molding, and heated in an oven at 60 ° C. for 4 hours to form a molded block. A release polyethylene terephthalate film was attached to the inner surface of the mold so that the release-treated surface was on the inside. The obtained molded block was sliced ​​to a desired thickness with a slicer in a direction perpendicular to the length direction of the molded block, thereby obtaining a thermally conductive sheet in which the carbon fibers were oriented in the thickness direction of the sheet. The numerical values ​​in Table 1 represent parts by mass unless otherwise specified.

[0081] [Dispersibility] In a thermally conductive composition in which components other than carbon fiber and thermally conductive fillers other than carbon fiber were mixed, carbon fiber and thermally conductive fillers other than carbon fiber were added one by one and stirred for 20 minutes, and it was visually evaluated whether or not the carbon fiber and thermally conductive fillers other than carbon fiber were dispersed in the thermally conductive composition. A planetary mixer (device name: Hivis Disper manufactured by Primix Corporation) was used for stirring, and the rotation speed was set to 20 rpm. When the carbon fiber and thermally conductive fillers other than carbon fiber were dispersed in the thermally conductive composition, it was evaluated as ◯ (OK), and when they were not dispersed, it was evaluated as × (NG). The results are shown in Table 1.

[0082] [Curability] The curability of the obtained thermally conductive sheet was evaluated. Specifically, when the thermally conductive composition was cured and could be formed into a sheet, it was evaluated as ◯ (OK), and when it was otherwise (for example, when the thermally conductive composition did not cure and could not be formed into a sheet, or when it was extremely weakly cured and deformed during processing into a sheet, making it difficult to handle), it was evaluated as × (NG). The results are shown in Table 1.

[0083] [Compression ratio] The compression ratio (initial compression ratio) of the obtained thermally conductive sheet was evaluated. Specifically, the thermally conductive sheet was cut to a predetermined size (20 mmφ×2000 μm thickness), and compressed under a pressure of 1 kgf / cm so that the average temperature of the thermally conductive sheet was 45° C. 2The thickness after stabilization (initial compressed thickness [μm]) was measured, and the compression ratio (%) was calculated according to the following formula 2. The results are shown in Table 1. Formula 2: Compression rate (%) = ((initial thickness of thermal conductive sheet - initial compressed thickness of thermal conductive sheet) / initial thickness of thermal conductive sheet) x 100

[0084] [Initial thermal conductivity] Using a thermal resistance measuring device conforming to ASTM-D5470, a load of 1kgf / cm 2 The initial thermal conductivity (W / m K) in the thickness direction of the thermal conductive sheet was measured by applying a voltage of 45°C. The sheet temperature during the measurement was 45°C. The results are shown in Table 1.

[0085] [Heat resistance reliability] The heat resistance reliability of the obtained thermally conductive sheet was evaluated. Specifically, the thermally conductive sheet was cut to a predetermined size (2 mm thick, 30 mm x 30 mm) and subjected to aging treatment (ultra-accelerated test) at 125°C for 500 hours or aging treatment (ultra-accelerated test) at 85°C and 85% relative humidity for 500 hours. The thermal conductivity was evaluated to be maintained by whether the thermal conductivity value of the thermally conductive sheet after aging treatment was 60% or more of the initial thermal conductivity value (before aging treatment). In other words, when the thermal conductivity maintenance rate calculated by the following formula 3 was 60% or more, it was evaluated that the thermal conductivity was maintained. The results are shown in Table 1. Equation 3: Thermal conductivity retention rate (%) = (thermal conductivity of thermal conductive sheet after aging treatment) / (initial thermal conductivity of thermal conductive sheet) × 100

[0086] [Flame retardant] The obtained thermally conductive sheet was subjected to a flame retardancy test in accordance with the UL-94 standard to evaluate its flame retardancy. That is, test pieces specified in UL-94 were prepared, and the obtained test pieces were subjected to a flame test based on the UL-94V vertical flame test method. The burning time is the sum of two ignitions and is the average of five test pieces. When the obtained results met the following UL-94 "V-2" grade criteria, they were evaluated as ◯ (OK), and otherwise they were evaluated as × (NG). The results are shown in Table 1. UL-94 "V-2": The average burning time after the ignition flame was removed was 30 seconds or less, and small flames capable of igniting absorbent cotton were dropped.

[0087] [Table 1]

[0088] The thermally conductive sheets of Examples 1 to 3 used thermally conductive compositions containing a binder component made of urethane resin, carbon fiber, a thermally conductive filler other than carbon fiber, a water absorbing agent, and a dispersing agent, in which the water absorbing agent contains zeolite and the content of the water absorbing agent is 2 to 15 parts by mass per 100 parts by mass of the binder component. As a result, it was found that the dispersibility of the composition, the hardening property of the composition, the compressibility of the sheet, the heat resistance of the sheet, the moisture resistance of the sheet, the initial thermal conductivity of the sheet, and the flame retardancy of the sheet were all good.

[0089] In Comparative Examples 1 and 2, it was found that the curing of the thermally conductive composition was inhibited, making it difficult to form the thermally conductive composition into a sheet. Therefore, in Comparative Examples 1 and 2, it was not possible to evaluate the compressibility, heat resistance reliability, initial thermal conductivity, and flame retardancy of the sheet.

[0090] In Comparative Example 3, it was found that the thermal conductive composition had poor dispersibility and was difficult to form into a sheet, and therefore, in Comparative Example 3, it was not possible to evaluate the compressibility, heat resistance reliability, initial thermal conductivity, and flame retardancy of the sheet. [Explanation of symbols]

[0091] 1 Thermally conductive sheet, 2 Binder component, 3 Carbon fiber, 3B carbon fiber, 4 Thermally conductive filler other than carbon fiber, 5 Insulating coating, 6 Insulating coated carbon fiber, 11 Release film, 50 Semiconductor device, 51 Electronic component, 52 Heat spreader, 53 Heat sink

Claims

1. a binder component made of a urethane resin; Carbon fiber, A thermally conductive filler other than carbon fiber; A water absorbent; and a dispersant, the dispersant is a titanate coupling agent, The thermally conductive filler other than the carbon fiber contains aluminum hydroxide, The water absorbing agent contains zeolite, The thermally conductive composition for a thermally conductive sheet, wherein the content of the water absorbing agent is 2 to 15 parts by mass per 100 parts by mass of the binder component.

2. The thermally conductive composition of claim 1 , wherein the water absorbing agent further comprises hydraulic alumina.

3. The thermally conductive composition according to claim 1 or 2, wherein the content of the silane-based dispersant is 0.1 mass % or less.

4. The thermally conductive composition according to any one of claims 1 to 3, further comprising a flame retardant.

5. A thermally conductive sheet comprising the thermally conductive composition according to any one of claims 1 to 4.

6. 45℃, load 1kgf / cm 2 The thermal conductive sheet according to claim 5 , wherein when pressure is applied thereto, the compressibility represented by the following formula 2 is 5% or more and 20% or less. Formula 2: Compressibility (%)=((initial thickness of the thermal conductive sheet−initial compressed thickness of the thermal conductive sheet) / initial thickness of the thermal conductive sheet)×100

7. A step A of preparing a thermally conductive composition by dispersing carbon fibers in a binder component made of a urethane resin; A step B of forming a molded block from the thermally conductive composition; and a step C of slicing the molded block into a sheet to obtain a thermally conductive sheet, The thermally conductive composition includes a binder component made of the urethane resin, the carbon fiber, a thermally conductive filler other than the carbon fiber, a water absorbing agent, and a dispersing agent, the dispersing agent being a titanate-based coupling agent, the thermally conductive filler other than the carbon fiber including aluminum hydroxide, and the water absorbing agent including zeolite, A method for producing a thermally conductive sheet, wherein the content of the water absorbing agent in the thermally conductive composition is 2 to 15 parts by mass per 100 parts by mass of the binder component.

8. A heating element; A heat dissipation member; 5. An electronic device comprising: a thermally conductive sheet comprising the thermally conductive composition according to claim 1, the thermally conductive sheet being disposed between the heat generating body and the heat dissipating member.

Citation Information

Patent Citations

  • Coating material composition for coating paper and coated paper using the same

    JP1998168358A

  • Heat-conductive resin composition and electronic component device using the same

    JP2003192913A

  • Two-pack type polyurethane-based adhesive

    JP2005089527A

  • Electroconductive resin composition

    JP2006036994A

  • Heat-radiating polyurethane resin composition and heat-radiating polyurethane sheet

    JP2008231348A